Quantitative analysis of 10 classes of phospholipids by ultrahigh-performance liquid chromatography tandem triple-quadrupole mass spectrometry - Huang, Qingxia (2020)
Phospholipids are the main constituents of biological membranes and their biological function has been increasingly recognized. Therefore, there is an unmet need to develop methods capable of quantifying a wide range of phospholipids with high sensitivities and high throughput. We employed an ultrahigh-performance liquid chromatography system coupled to a triple-quadrupole mass spectrometer (UHPLC-MS) and developed a method that can quantitatively analyze 10 major classes of phospholipids in biological samples in 11 min. These are phosphatidic acid, phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylserine, sphingomyelin, lysophosphatidic acid, lysophosphatidylcholine and lysophosphatidylethanolamine. The limit of detection (LOD) and limit of quantitation (LOQ) are 0.04–33 pmol mL−1 and 0.1–110 pmol mL−1, respectively. The method takes three steps: first and second steps identified phospholipid structures in a mixture containing aliquots of all the samples using the combinations of multiple reaction monitoring (MRM), product ion scan and retention time in the positive and negative ion modes. These steps enabled the identification of phospholipids present in the samples and provided information on efficient sample analysis in the final step of sample quantitative analysis. We have developed fast and sensitive label-free quantitation with normalization of the acyl chain length to achieve more accurate quantification. The method developed was applied to analyze 6 different biological samples (plasma, cells and tissues) for applicability validation, where a total of 308 phospholipid species across 10 phospholipid classes were identified and 295 phospholipid species were quantified. The method is highly efficient, sensitive, and is universally applicable.